Salvage Glue Embolization of Iatrogenic Alveolar-Pleural Fistula Following Lung Ablation - Li, Yan-Lin; Preston, Emma; Lyon, Paul C.; Anderson, Ewan M. (Journal of Clinical Interventional Radiology ISVIR, 2024)
A 76-year-old smoker was referred to the interventional radiology team for thermal ablation of a solitary colorectal pulmonary metastasis. He underwent percutaneous microwave ablation that was complicated with extensive surgical emphysema due to an alveolar-pleural fistula. Percutaneous computed tomography (CT) guided glue embolization was performed resulting in fistula occlusion and resolution of surgical emphysema.
Keywords: interventional oncology; lung ablation; alveolar-pleural fistula